Factors Affecting on Satisfaction of Home Stay Foreign Tourist in Kandy Sri Lanka (Global Journal of Management and Business Research, 2019)
This paper is an endeavor to examine the factors affecting the satisfaction of homestay tourists. This study was conducted based on the tourists' homestays located in Kandy Sri Lanka. The paper reviews the literature on the satisfaction of tourists, demographic reasons for selecting Kandy and the impact of destination attributes to satisfaction, such as; service, security, facility and price level. In addition, the paper intends to test the relationship between tourists' satisfaction and the demographic characteristics. In the light of the findings, it will benefit to the government to identify the developments of homestay concept and tourism industry. The findings of this study will also be valuable to the hospitality industry and entrepreneurs to make improvements in the field, thus, by engaging in numerous marketing and promotional activities to attract tourist as well as by improving their satisfaction.
Keywords: homestays; satisfaction; tourists; kandy